Girişimci Gazetecilik-Serbest Gazetecilik Karşılaştırmalı Bir Tartışma - ÖZAY, SEÇİL (My University, 2022)
Innovations in the area of communication and informatics in the 21st century have affected the media world; the changes and transformations which are taking place have also transformed the professions of journalism. Thus, new channels for publishing and content types have emerged. These emerging new channels and content types have also brought new journalism types up for discussion. The main discussion of this study is formed within the framework of the concept of entrepreneurial journalism, which is suggested for journalists to adapt to these new conditions. Entrepreneurial journalism came into prominence when the media sector was going through difficult times and was declared as the savior of the sector in a way. In the most general sense, it is stated as development of a new product, service or publishing medium; or creation of new business models by journalists. Entrepreneurial journalism has created a new space where journalists can create new business models, start businesses and become their own bosses. However, there are supporters of the idea that entrepreneurial journalists are not much different from freelance journalists, who are already important members of the media. In this study, which is based on literature review, it is aimed to explain the concepts of “Entrepreneurial Journalism” and “Freelance Journalism” and to discuss the connection points and differences of the two concepts. The main objective of this study is to clearly define the boundaries of the concepts of entrepreneurial journalism and freelance journalism by drawing on the literature. Keywords: Journalism, Freelance Journalism, Entrepreneurial Journalism

21. yüzyılda iletişim ve bilişim alanında yaşanan yenilikler medya dünyasını etkilemiş, bu alandaki değişim ve dönüşümler gazetecilik uygulamalarını da dönüştürmüştür. Böylece yeni yayıncılık mecraları ve içerik türleri ortaya çıkmıştır. Bu yeni yayıncılık mecraları ve içerik türleri gazetecilik uygulamalarındaki bu yeni yönelimlerim de açıklanması ihtiyacını doğurmuştur. Bu çalışmanın temel tartışması gazetecilerin bu yeni şartlara uyum sağlaması için önerilen girişimci gazetecilik kavramı çerçevesinde biçimlenmektedir. Girişimci gazetecilik medya sektörünün ekonomik olarak zor zamanlardan geçtiği dönemlerde ön plana çıkmış ve bir bakıma sektörün kurtarıcısı olarak ilan edilmiştir. Girişimci gazetecilik, en genel anlamıyla gazetecilerin yeni bir ürün, hizmet veya yayıncılık mecrası geliştirmesi; yeni iş modelleri oluşturması biçiminde ifade edilmektedir. Gazetecilerin yeni iş modelleri oluşturabildikleri, işletmeler kurdukları ve kendi işlerinin patronu olabildikleri yeni bir alan olarak literatürde yer bulan girişimci gazeteciliğin hali hazırda haber medyasında önemli çalışma biçimi olan serbest gazetecilikten çok da farklı olmadığını savunanlar bulunmaktadır. Literatür taramasına dayalı bu çalışmada “Girişimci Gazetecilik” ve “Serbest Gazetecilik” kavramlarının açıklanması ve iki kavramın bağlantı noktaları ile karşıtlıklarının tartışılması amaçlanmıştır. Bu çalışmanın temel hedefi, literatürden yararlanarak girişimci gazetecilik ve serbest gazetecilik kavramlarının sınırlarının net olarak ortaya konması oluşturmaktadır. Anahtar Kelimeler: Gazetecilik, Serbest Gazetecilik, Girişimci Gazetecilik
Entrepreneurial Journalism-Freelance Journalism A Comparative Discussion
Keywords: Gazetecilik; Serbest Gazetecilik; Girişimci Gazetecilik; Journalism; Freelance Journalism; Entrepreneurial Journalism